KEMAMPUAN PSEUDOMONAS KELOMPOK FLUORESCENS DALAM MENINGKATKAN KETAHANAN TERHADAP INFEKSI VIRUS KERITING KUNING SERTA MEMACU PERTUMBUHAN TANAMAN CABAI BESAR - Mursiana, Mursiana; Aidawati, Noor; Adriani, Dewi Erika (EnviroScienteae, 2021)
This study aimed to 1) Analyze several Pseudomonas fluorescens groupâ€™s ability to induce resistance of chili plants to yellow curly virus infection. 2) Analyzing the ability of several Pseudomonas fluorescens groups to stimulate the growth of chili plants. The experimental design used a completely randomized design (CRD) with four levels of treatment, namely : control (untreated chili plants), SKM1 (chili plants treated with Pseudomonas fluorescens group SKM1), MP1 (chili plants treated with Pseudomonas fluorescein group MP1), and MM2 (chili plants treated with Pseudomonas fluorescens group MM2). Bacterial treatment was carried out by immersing chili seeds into a solution of the Pseudomonas fluorescens group with a concentration of 109 CFU/ml. Virus transmission in chili plants was carried out naturally in areas of high yellow curly disease epidemics. The results indicated that chili plants treated with Pseudomonas fluorescens groups SKM1, MM2, and MP1 had increased resistance to yellow curly virus infection and decreased percentage of attacks from yellow curly virus disease. Chili plants treated with Pseudomonas fluorescens group MM2 showed higher plantâ€™s height and more branches than those treated with SKM1, MP1, and control. Chili plants treated with Pseudomonas fluorescens groups MM2 and MP1 have faster flowering time than those treated with SKM1 and control.Â